2007
DOI: 10.1128/iai.01013-06
|View full text |Cite
|
Sign up to set email alerts
|

Role for Gingipains inPorphyromonas gingivalisTraffic to Phagolysosomes and Survival in Human Aortic Endothelial Cells

Abstract: Gingipains are cysteine proteinases that are responsible for the virulence of Porphyromonas gingivalis. Recent studies have shown that P. gingivalis is trapped within autophagic compartments of infected cells, where it promotes survival. In this study we investigated the role of gingipains in the intracellular trafficking and survival of this bacterium in human aortic endothelial cells and any possible involvement of these enzymes in the autophagic pathway. Although autophagic events were enhanced by infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 57 publications
4
69
0
Order By: Relevance
“…7 On the other hand, no bacteria were found in the cytoplasmic spaces of endothelial cells. 11,12 We showed that P. gingivalis is internalized in early endosomes and about half of the intracellular bacteria were found to be sorted to lytic compartments, including autolysosomes and late endosomes/lysosomes. 6 Intracellular trafficking of P. gingivalis may depend on the phenotypic and cells in a mechanism of cell-to-cell spreading (Fig.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
See 1 more Smart Citation
“…7 On the other hand, no bacteria were found in the cytoplasmic spaces of endothelial cells. 11,12 We showed that P. gingivalis is internalized in early endosomes and about half of the intracellular bacteria were found to be sorted to lytic compartments, including autolysosomes and late endosomes/lysosomes. 6 Intracellular trafficking of P. gingivalis may depend on the phenotypic and cells in a mechanism of cell-to-cell spreading (Fig.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…Intracellular P. gingivalis reportedly localizes in various cellular compartments, such as the cytoplasm, 7-10 endosomes, [8][9][10][11][12] and autophagosomes, [11][12][13] which are distinctive double-membraned vacuoles that are part of the autophagic pathway, with autophagosome localization noted to occur in endothelial and smooth muscle cells, 11 but not in gingival epithelial cells. 7 On the other hand, no bacteria were found in the cytoplasmic spaces of endothelial cells.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…The mouse NIH/3T3 fibroblast cell line was purchased from the American Type Culture Collection (ATCC) and cultivated in DMEM supplemented with 10% FCS. P. gingivalis strain ATCC 33277 is fimbriated and has high gingipain activity; both virulence factors are required for successful attachment and internalization (47)(48)(49). P. gingivalis was cultured as described previously (7).…”
Section: Methodsmentioning
confidence: 99%
“…Gingipains consist of two molecular species that show differing substrate specificity: Arg-specific (Rgp) and Lys-specific (Kgp) enzymes. 14) These enzymes are essential for the growth and survival of the bacterium in vitro and in vivo, [15][16][17][18] and play critical roles in the degradation of host proteins [19][20][21] and cell invasion by the bacterium. 22,23) Gingipains are the major determinants in the pathogenicity of P. gingivalis, so that inhibitory agents towards these enzymes can be expected to be effective in preventing and improving P. gingivalis-associated diseases.…”
mentioning
confidence: 99%